2019
DOI: 10.14309/01.ajg.0000593392.14697.54
|View full text |Cite
|
Sign up to set email alerts
|

964 Patient Flow Across Physician Specialties Over the Course of the Hepatitis C Care Cascade: A Real World Analysis From the United States

Abstract: INTRODUCTION: Hepatitis C virus (HCV) infection is a major cause of hepatic and extrahepatic morbidity and mortality. In spite of recommendations for HCV screening, diagnosis, linkage to care and treatment, significant gaps remain in the cascade of care for HCV. As the role of physician specialties for closing these gaps is poorly understood, this study assesses the flow of HCV patients across physician specialties in the US, over the course of the care cascade. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This may be because of the relatively high cost of the treatment or the fact that GPs are not adequately trained to treat these patients. 49 However, GPs must be seen as a valuable resource to extend screening and treatment capacities, 13,50 especially given that pangenotypic regimens have simplified HCV treatment in recent years and the fact that in most cases genotyping is not necessary. 15 Of note, one study suggested that financial incentives can improve screening rates for GPs.…”
Section: S Pecifi Che Althsys Tembarrier S Integ R Ated C Are Pathwa...mentioning
confidence: 99%
“…This may be because of the relatively high cost of the treatment or the fact that GPs are not adequately trained to treat these patients. 49 However, GPs must be seen as a valuable resource to extend screening and treatment capacities, 13,50 especially given that pangenotypic regimens have simplified HCV treatment in recent years and the fact that in most cases genotyping is not necessary. 15 Of note, one study suggested that financial incentives can improve screening rates for GPs.…”
Section: S Pecifi Che Althsys Tembarrier S Integ R Ated C Are Pathwa...mentioning
confidence: 99%
“…As an illustrative example, Rege et al found in an analysis of two large national laboratory databases from 2013 to 2016, that 89.4% of patients diagnosed with chronic HCV infection did not receive prescription for antiviral therapy. In this study, 46.7% of patients did not have genotype testing, and 57.3% did not have liver chemistries, suggesting that patients suffer attrition at an early phase of the care cascade . Future work to target the care cascade gaps will help to identify those for whom treatment could be offered: HCV screening, diagnosis, patient communication regarding chronic infection, care linkage, and fibrosis staging.…”
Section: Hepatitis C: From Chronic Malady To Robust Curementioning
confidence: 85%
“…In this study, 46.7% of patients did not have genotype testing, and 57.3% did not have liver chemistries, suggesting that patients suffer attrition at an early phase of the care cascade. (31) Future work to target the care cascade gaps will help to identify those for whom treatment could be offered: HCV screening, diagnosis, patient communication regarding chronic infection, care linkage, and fibrosis staging. Concurrently, development of HCV vaccinations and subsequent provision implementation strategies will be important to reduce population disease burden.…”
Section: Future Directionsmentioning
confidence: 99%
“…One reason for this is that care pathways have been unnecessarily complex including multiple investigations prior to treatment, which leads to patients frequently being lost to follow up and never completing treatment. Attrition appears to occur early in the treatment cascade; in one study 57.3% of patients dropped off prior to having liver enzymes checked[ 83 ]. With the advent of pangenotypic regimens and simple non-invasive fibrosis scores [ e.g., fibrosis-4 (FIB-4) and aminotransferase-platelet ratio index] pathways can effectively be simplified, which is likely to reduce attrition.…”
Section: Hepatitis C Virusmentioning
confidence: 99%